Foreign aid instability and bundled governance dynamics in Africa - Asongu Simplice; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
Purpose- With the recent financial crisis and reduction of foreign aid by donor countries, the aid-institutions debate is shifting to how aid instability affects governance in developing countries. We engage the policy debate by assessing the role of foreign aid instability on governance dynamics in fifty three African countries for the period 1996-2010. Design/methodology/approach- An autoregressive endogeneity-robust Generalized Methods of Moments is employed. Instabilities are measured in terms of standard errors and standard deviations. Three main aid indicators are used, namely: total aid, aid from multilateral donors and bilateral aid. Principal Component Analysis is used to bundle governance indicators, namely: political governance (voice & accountability and political stability/non violence), economic governance (regulation quality and government effectiveness), institutional governance (rule of law and corruption-control) and general governance (political, economic and institutional governance). Findings- Our findings show that foreign aid instability increases governance standards, especially political and general governance. Practical implications- In the presence of foreign aid instability, governments could be constrained to improve governance standards in exchange for, or anticipation of greater dependence on local tax revenues. Moreover, bundling governance indicators improves insights into how macroeconomic variables affect governance. This is essentially because, while aid instability improves general governance, for the most part it is not consistently for economic and institutional governance. Originality/value- The paper has contributed to the aid-institutions' literature by examining how aid instabilities affect an aggregate index of governance dynamics in Africa.
Keywords: C53; F35; F47; O11; O55; 330; Instability; Foreign aid; Governance; Development; Africa